Perfusion and plaque evaluation to predict recurrent stroke in symptomatic middle cerebral artery stenosis - Ning Ma; Lin Ma; Feng Xu; Xin Zhou; Jinhao Lyu; Chenglin Tian; Hang Shao; Xin Lou (Stroke and Vascular Neurology, 2019)
Background and purpose We investigated the baseline demographics of patients with severe unilateral atherosclerotic stenosis of the middle cerebral artery (MCA) using multimodal MRI and evaluated the haemodynamic impairments and plaque characteristics of patients who had a recurrent stroke.Materials and methods We retrospectively recruited consecutive patients with severe unilateral atherosclerotic MCA stenosis who underwent arterial spin labelling (ASL) with postlabelling delay (PLD) of 1.5 and 2.5 s, and vessel wall MRI. For each PLD, cerebral blood flow (CBF) maps were generated. Hypoperfusion volume ratio (HVR) from 2 PLD CBF was calculated. An HVR value ≥50% was considered as severe HVR. Plaque areas, plaque burden, plaque length and remodelling index were measured. Plaque enhancement at maximal lumen narrowing site were graded. Baseline clinical and imaging characteristics were compared between patients with (event+) and without (event−) 1 year ischaemic events.Results Forty-three patients (47.23±12.15 years; 28 men) were enrolled in this study. Seven patients had an HVR ≥50%. During the 1-year follow-up, 7 patients had experienced a recurrent stroke. HVR were significantly higher in the event+ than event− (53.17%±29.82% vs 16.9%±15.57%, p=0.0002), whereas no significant difference was detected in plaque areas, plaque burden, remodelling index, plaque length and plaque enhancement grade. The multivariable analysis revealed that a severe HVR was significantly associated with a recurrent stroke (Odds ratio=12.93, 95% confidence interval 1.57 to 106.24, p=0.017) after adjusted by hypertension and smoking.Conclusion HVR obtained from two PLD ASL may be a useful imaging predictor of recurrent stroke.